The calling of kindred : Poems from the english-speaking world - Barlow, Adrian (New York : Cambridge University press, 2000)
A collection of literature anthologies and reference books for Key Stage 3 onwards
Includes index.
Keywords: English poetry; Poésie anglaise; Poetry -- Collections